Barriers to Public Participation in Urban Green Infrastructure in China from Stakeholders’ and Residents’ Perspective, A Case Study in Yangzhou - Xiao, Yiping (International Journal of Social Sciences and Public Administration, 2024)
Public participation has always played an important role in urban design and planning. Urban green infrastructure is a part of urban planning and design. This research uses a policy review and semi-structured interviews with residents and stakeholders. The findings suggest that the lack of public participation in urban green infrastructure projects is the result of a combination of both government and the general public. Residents have low interest in participating in urban green infrastructure due to social cultural, public competence and lack of community spirit. Stakeholders have tried to avoid public participation in projects due to limited participation methods and limited project timeline. Citizen participation can be increased through improved technical support, media advocacy and legislation and regulations.